2010
DOI: 10.1097/brs.0b013e3181d81a96
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Dysphagia in Anterior Cervical Spine Surgery

Abstract: A better understanding of dysphagia will require the development of better outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
3
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 19 publications
5
106
3
8
Order By: Relevance
“…The severity and potential life-threatening nature of these complications from anterior cervical spinal surgery have prompted more thorough evaluations of their incidence and associated risk factors. 3,6,9,11,13,19,24,[27][28][29]33 The reported rates of dysphagia after anterior cervical surgery have varied widely, from 1% to 79%. 9 In a prospective study, Lee et al 19 found the prevalence of postoperative dysphagia at 1, 2, 6, 12, and 24 months to be 54%, 34%, 19%, 15%, and 14%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The severity and potential life-threatening nature of these complications from anterior cervical spinal surgery have prompted more thorough evaluations of their incidence and associated risk factors. 3,6,9,11,13,19,24,[27][28][29]33 The reported rates of dysphagia after anterior cervical surgery have varied widely, from 1% to 79%. 9 In a prospective study, Lee et al 19 found the prevalence of postoperative dysphagia at 1, 2, 6, 12, and 24 months to be 54%, 34%, 19%, 15%, and 14%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of the previously published series, dysphagia and dysphonia are the most common postoperative complications, with rates ranging from 1-79% (16,45). This wide variation may be partially explained by the fact that dysphagia is routinely underestimated as a complication (21,25,66).…”
Section: Dysphagiamentioning
confidence: 99%
“…Implant related complications have also been reported in the literature (20,27,(40)(41)(42)(43)(44). The list also includes functional complications such as dysphagia, dysphonia, and difficulty in swallowing (7,(45)(46)(47)(48)(49)(50)(51). Although the vast majority of these complications are of minor clinical impact, there are extremely rare occasions that the outcome of a complication may be troublesome or even fatal.…”
Section: Introductionmentioning
confidence: 99%
“…4,7 Among these, dysphagia has been a consistently recognized early complication following anterior cervical spine surgery, and its reported incidence is highly variable, ranging from 1% to as high as 79%. 2,3,5,6,10,14,22,24,28,33 This variation is in part attributed to how dysphagia is defined by investigators and the threshold of severity at which it is considered to be a complication. Fortunately, most studies show dysphagia to be typically a transient phenomenon following anterior cervical surgery.…”
mentioning
confidence: 99%